Comparative hypoglycemic activity of different extracts of Teucrium stocksianum in diabetic rabbits (Bangladesh Journal of Pharmacology, 2013)
In the present study crude powder and various extracts of Teucrium stocksianum were evaluated for antidiabetic effect in alloxan-induced diabetic rabbits. Crude extract significantly reduced blood glucose level of normal and diabetic rabbits. The results were comparable with standard drug gliben-clamide. Ethyl acetate extract (500 mg/kg) produced maximum decrease in blood glucose level among all the extracts and was selected for further study. Ethyl acetate extract significantly inhibited rise in glucose level in normal rabbits after an oral glucose load. The extract showed synergistic effect with different doses of insulin. Serum insulin level of diabetic rabbits was also significantly increased by the extract. HbA1c level was significantly (p